2008
DOI: 10.1016/j.jneuroling.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Second-language learning and changes in the brain

Abstract: Presumably, second-language (L2) learning is mediated by changes in the brain. Little is known about what changes in the brain, how the brain changes, or when these changes occur during learning. Here, we illustrate by way of example how modern brain-based methods can be used to discern some of the changes that occur during L2 learning. Preliminary results from three studies indicate that classroom-based L2 instruction can result in changes in the brain's electrical activity, in the location of this activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 31 publications
12
129
1
Order By: Relevance
“…These results suggest that the two subgroups of L2 learners may have obtained different ERP signatures as a result of attaining different structurespecific proficiencies. McLaughlin et al (2010), Osterhout et al (2006), and Osterhout et al (2008) found similar ERP differences when dividing participants into subgroups of more accurate and less accurate L2 learners based on grammaticality judgment tasks. Similarly, Reichle (2010a) found increased positivities for correct responder subgroups versus incorrect responder subgroups on an acceptability task for anomalies in the syntactic constructions used to mark focus structure in native and L2 French.…”
Section: Event-related Potentials and L2 Proficiencymentioning
confidence: 75%
See 1 more Smart Citation
“…These results suggest that the two subgroups of L2 learners may have obtained different ERP signatures as a result of attaining different structurespecific proficiencies. McLaughlin et al (2010), Osterhout et al (2006), and Osterhout et al (2008) found similar ERP differences when dividing participants into subgroups of more accurate and less accurate L2 learners based on grammaticality judgment tasks. Similarly, Reichle (2010a) found increased positivities for correct responder subgroups versus incorrect responder subgroups on an acceptability task for anomalies in the syntactic constructions used to mark focus structure in native and L2 French.…”
Section: Event-related Potentials and L2 Proficiencymentioning
confidence: 75%
“…Recent work suggests that adult late L2 learners are indeed able to display native-like ERP effects at sufficiently high levels of proficiency (e. g., Gillon Dowens et al 2010;McLaughlin et al 2004McLaughlin et al , 2010Ojima et al 2005;Osterhout et al 2006Osterhout et al , 2008Steinhauer et al 2006;Tanner et al 2009). …”
Section: Event-related Potentials and L2 Proficiencymentioning
confidence: 99%
“…Based on previous studies about bilingualism, lower L2 proficiency results in weaker semantic processing (Ojima, Nakata, & Kakigi, 2005;Sagarra & Herschensohn, 2011) and syntactic processing (Ojima et al, 2005;Osterhout et al, 2008;Rossi, Gugler, Friederici, & Hahne, 2006;Sagarra & Herschensohn, 2010Steinhauer, White, & Drury, 2009). The efficiency of working memory is partially dependent on proficiency (van den Noort, Bosch, & Hugdahl, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…But studies such as Osterhout et al (2008) suggest that changes in the brain may start even in the earlier stages of language learning. This has implications not only for recognizing the value of partial language competences, but also for understanding why certain approaches such as CLIL appear to lead to positive learning outcomes.…”
Section: Convergence Of Insights From the Neurosciencesmentioning
confidence: 99%